PENGARUH SISTEM INFORMASI BERBASIS WEB DAN KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH PADA PT. PEGADAIAN (PERSERO) DI KOTA BATAM - Mesri Silalahi (Universitas Putera Batam, 2013)
This study was conducted to determine how the image of a web-based information system utilization by clients of PT. Pegadaian (Persero) in Batu Aji Batam Branch, how is the quality of service, how the level of client satisfaction, how the influence of web-based information systems PT. Pegadaian (Persero) in Batu Aji Batam Branch on customer satisfaction, impact of service quality on customer satisfaction as well as the influence of web-based information systems and service quality on customer satisfaction PT. Pegadaian (Persero) in Batu Aji Batam Branch. Collecting data by distributing questionnaires to all customers by assuming the entire customer population is listed as a member. Data processing using statistical program SPSS to analyze the data using descriptive quality of the test data, the hypothesis testing, simultaneous test (F) and partial test (T). The findings of this study is the quality of service to customers of PT. Pegadaian (Persero) in Batu Aji Batam Branch good, the customer has a fairly high level of satisfaction, a web-based information systems affect customer satisfaction, service quality PT. Pegadaian (Persero) in Batu Aji Batam Branch affect customer satisfaction, web-based information systems and service quality affect customer satisfaction PT. Pegadaian (Persero) in Batu Aji Batam Branch.